Advancing the Field of Pediatric Exercise Oncology: Research and Innovation Needs - Wurz Amanda; McLaughlin Emma; Viña Carolina Chamorro; Grimshaw Sarah L; Hamari Lotta; Götte Miriam; Kesting Sabine; Rossi Francesca; van der Torre Patrick; Guilcher Gregory MT; McIntyre Krista; Culos-Reed S Nicole (MDPI, 2022)
The field of pediatric exercise oncology explores the relationships between physical activity (PA), including exercise, and a range of outcomes among children and adolescents affected by cancer. Although PA is safe and beneficial for this population, several important gaps in knowledge and practice remain. In this article, we describe research and innovation needs that were developed with a team of international experts and relevant literature, a series of online surveys, and an in-person meeting. Addressing these needs will contribute valuable knowledge and practice outputs to advance this field, ultimately enabling a greater number of children and adolescents affected by cancer to realize the benefits of moving more.